Pengaruh Sosial Media Marketing Terhadap Brand Awareness Dan Loyalitas Pelanggan - Laoli, Viktorman; Mendrofa, Zakaria Abadi; Mendrofa, Selvinus Berkat Totonafo (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
Digital marketing has become one of the most effective strategies in influencing consumer behavior inthis digital era. Social media platforms, as one of the main marketing channels, play an important role in shaping consumer purchasing decisions. This study aims to analyze the impact of digital marketing, particularly through social media, on consumer behavior. The method used in this study is a surveyof 200 consumers who are active on social media, focusing on the use of platforms such as Instagram, Facebook, and TikTok. The results show that relevant content and direct interaction between brands and consumers have a significant influence on purchasing decisions. The findings provide insights forcompanies to design more effective marketing strategies in the digital era.